Implementasi Raspberry Pi Sebagai IP Kamera untuk Memonitoring Studio Bioskop - Sugiyatno, Sugiyatno; Suroso, Amat (Puslitbang Kopertip Indonesia, 2017)
In the show the film in theaters 21 cineplex currently in need of a centralized monitoring system. However, the monitoring systems currently running in theaters only operates locally only areaand also less effective the current system is, because the output can not be configured as needed, therefore needed an alternative solution to address all of these problems, One alternative solution is to utilize the raspberry pi as ip camera. Raspberry pi is a mini PC that has a lot of advantages which are as intelligent IP cameras in because the raspberry pi using an operating system or so-called mini debian Raspbian,thus allowing raspberry pi can be configured to suit your needs and can be integrated with the NOC (Network Operations Center) which is currently still under construction.Thus 21cineplex theater company has been getting an alternative solution to the above problems.